Finding Home: Landmark Ambiguity in Human Navigation - Jetzschke, Simon; Ernst, Marc O.; Froehlich, Julia; Boeddeker, Norbert (Frontiers in Behavioral Neuroscience, 2017)
Memories of places often include landmark cues, i.e. information provided by the spatial arrangement of distinct objects with respect to the target location. To study how humans utilize landmark information for navigation we conducted two experiments. Participants were either provided with auditory landmarks while walking in a large sports hall or with visual landmarks while walking on a virtual-reality treadmill setup. We found that participants cannot reliably locate their home position when only one or two uniform landmarks provide cues with respect to the target. With three visual landmarks that look alike, the task is solved without ambiguity, whereas audio landmarks need to play three unique sounds for a similar performance. To examine how landmark cues are combined we introduced systematic conflicts in the visual landmark configuration between training of the home position and tests of the homing performance. The participants integrated the spatial information from each landmark near-optimally to reduce spatial variability. When the conflict becomes big, this integration breaks down and precision is sacrificed for accuracy. That is, participants return again closer to the home position, because they start ignoring the deviant third landmark. Relying on two instead of three landmarks however, goes along with responses that are scattered over a larger area, thus leading to higher variability. A probabilistic model with no free parameters can predict this integration performance. The only parameters of the model were fixed based on the homing performance to the baseline condition which contained a single landmark. Overall these data suggest that humans use similar optimal strategies in visual and auditory navigation, combining landmark information to improve homing precision and balance homing precision with homing accuracy.